Design of Air Blast Freezing System Using Cascade Refrigeration R290/R32 System with Capacity 5kg - Martin, Awaludin; Nasution, Fikri Fahlevi; Mainil, Rahmat Iman (Journal of Ocean, Mechanical and Aerospace -science and engineering-, 2024)
Indonesia is a maritime country that has an abundance of marine catches. In 2022, the production of marine catches reached 24.85 millions tons, while the export amount was 1.221 millions tons. This is due to the limited technology that can extend the freshness of marine catches. Based on this problem, a cooling system was designed in the form of an ABF that can freeze marine catch products. The Air Blast Freezing (ABF) system is designed at an air temperature of -40oC using a cascade refrigeration system. The working fluid used is R290/R32 hydrocarbon, which has very low GWP and ODP so it is safe for the environment and the earth's ozone layer. The results obtained show that the cooling load is 444.037 Watts, the LTC compressor power and HTC compressor power are 116.19 Watts and 205.98 watts. The designed air blast freezing system has a surface area of LTC evaporator of 2.670 m2 and HTC condenser of 4.780 m2. The calculated capillary pipe length is 1.94 m for HTC and 1.51 m for LTC, the COP of the ABF system is 2.774.